Korelasi Perilaku Kedisiplinan dengan Karakter Religius Siswa MAN Se-Kabupaten Kampar - Delviany, Venny; Zein, Mas’ud; Anwar, Khairil (MASALIQ, 2025)
This research aimed to examine the correlation between discipline and religious character of MAN students within Kampar Regency. This research was carried out with quantitative-correlational approach. The population were all students of MAN 1 Kampar amounted 633 students, all students of MAN 2 Kampar amounted 212 students, and all students of MAN 4 Kampar amounted 232 students with total populations were 1077 students and the samples were 531 students. The sampling technique was by using simple random sampling. The technique of data collection was by using questionnaire. The data analysis technique used pre-requisite questionnaire test instrument: validity and reliability test, correlation test: normality test and linearity test, and research hypothesis test: bivariate correlation test. The results of this research: there was positive and significant correlation between discipline behavior with religious character. Obtained the value of sig. (2 tailed) 0,000 < 0,050 which meant Ho was rejected and Ha was accepted. With R value = 0,551 pearson correlation in correlation degree which meant it was in medium level.